Augusto Emilio Zaluar e os homens sem senhor: Vida cotidiana na peregrinação pela província de São Paulo, 1860 - 1861 - Dias, Alan Modesto (2006)
The dissertation analyzes the daily routine of poor and free men conductors, small grocers, leprous, women and hillbillies described by the Portuguese writer Augusto Emílio Zaluar, in his written literary work Peregrinação pela Província de São Paulo, 1860 1861. (Peregrination through the Province of São Paulo). His documentary scope is based on trip accounts from the 19th century, work manuscripts and letters from the Agricultural Congress of Rio de Janeiro in 1878. The dissertation is divided into 3 chapters as following. The first chapter goes over the universe of particularities that establish the process of repeated visits of the Portuguese America, the intentions of foreign travelers from the 19th century, as well as their assessment prospect before the values and customs of poor and free men. The second chapter goes over the peculiarities of the roads between small cities from countryside and conductors and small grocer s daily routine. The third chapter goes over the urban scenery and the daily routine of leprous, women and hillbillies